Slowly progressive apraxia in Alzheimer's disease. - Green, R C (1995)
Slowly progressive apraxia due to Alzheimer's disease was encountered in a 66 year old, right handed man whose initial impairments included coordinated movements of the left hand and some features of the alien hand syndrome. Over four years, the patient developed progressively worsening deficits of memory and language. A biopsy of his right temporal lobe showed numerous plaques and neurofibrillary tangles. Pronounced right parietal lobe hypoperfusion on serial SPECT suggests involvement of this region in contralateral praxis.